Servant Leadership Stimulates Spiritual Well-Being Through Team Trust in a Female Religious Context - Obi, Innocentina-Marie; Aaldering, Hillie; Bollen, Katalien; Euwema, Martin Claes (Frontiers in Psychology, 2021)
This study investigates how female religious leaders nurture spiritual wellbeing in religious sisters. Specifically, we examined how servant leadership fosters spiritual wellbeing (Gifts and Fruits of the Spirit) through respectively the mediating role of team trust and reduced occurrence of team conflicts. Quantitative survey data were collected from 453 religious sisters (followers) within a Catholic Women Religious Institute in Nigeria. Using structural equation modelling, results showed that servant leadership is positively related to team trust and negatively related to team conflict. Further findings showed that servant leadership indirectly fosters spiritual wellbeing through the mediating role of team trust, however not through reduced team conflict. Theoretical and practical implications are discussed. Keywords: Servant leadership, team trust, team conflict, spiritual wellbeing, convent.